A comparison of classic and skate cross-country skiing in varying terrain employed by male and female world-class skiers - Bolger, C.; Hegge, A. M.; Kocbach, J.; Sandbakk, O. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Cross-country skiing evolved from the single classical style to two separate techniques, classic and skate. Skiers train to perform both styles on similar tracks with varying terrain. Extensive sprint race analyses have been done, whereas distance races have been examined to a less extent and no previous study has directly compared the skating and classic techniques during actual competitions. Therefore, the present study compared speed and heart rate profiles of world-class skiers during an international competition on varying terrain in the skating and classical technique. From here, we analyzed possible differences between classic and skate, and the magnitude of gender differences. Methods: Four male and five female world-class cross-country skiers from the Norwegian national team participated in individual time-trials of 15 (men) and 10 km (women) on two consecutive days with comparable conditions on the same course for classic and skate. The skiers` heart rate and location were continuously monitored by a Garmin GPS monitor, and integrated with a calibrated standard track profile. Time, speed and heart rate for uphill, flat, downhill and turn sections of the overall races and on each consecutive 5 km lap were determined. Results: The average speed was 10 and 9% higher in skating than in classic for men and women, respectively; with corresponding numbers of 12 and 11% for uphill, 7 and 13% for flat and 2 and 1.5% for downhill terrain. Men were 9, 11 and 4% faster than women on uphill, flat and downhill terrain in classic and 11, 6 and 5% in skating. On average, heart rate increased by approximately 10 bpm during ~1.5 min uphill skiing and was relatively stable throughout the flat sections in both techniques. There was a trend towards greater heart rate decreases during the downhill sections for classic compared to skating. Conclusion: For the first time, the current study compared the speed and heart rate profiles during international skating and classic competitions in elite cross-country skiers. The ~10% difference between techniques for both genders was slightly less than expected; men showed greatest differences in uphill terrain, whereas women tended to have the greatest differences on the flat. The effect of terrain on gender differences may be associated with differences in the upper and lower limb distribution. Uphill skating and flat classic skiing are thought to have the most effective poling, whereas flat terrain in skating allows women to utilize the legs more. There were modest differences in downhill sections between techniques and gender. However, heart rate decreased less during skating downhill, which might be associated with leg contribution from the skating push-offs in this terrain.